A simulation-based optimisation approach for multi-objective inventory control of perishable products in closed-loop supply chains under uncertainty. (2018) - Hasani, Aliakbar; Eskandarpour, Majid; Fattahi, Mohammad
This paper investigates the inventory control of perishable products with a limited storage lifetime in closed-loop supply chains. Uncertainties related to customers' demands, the return rate of goods, and qualities of the returned products are considered. An efficient interactive response surface methodology is adopted by using a statistical simulation approach. The desirability function is taken into account a minimum desirability level of multiple objectives, the potential correlation between the considered objectives, and minimisation of uncontrollable variables or noise factors effect. The experimental results indicate the efficiency of the proposed simulation-based optimisation approach in handling correlated multiple objectives for inventory control of perishable products in closed-loop supply chains under uncertainty. Considered risks in the supply chain echelons and fair costs allocation has been balanced efficiently via using the proposed interactive approach to solving the multi-objective problem. Finally, the robustness of the obtained solutions is assessed under variation in weights of the response variables.